2018
DOI: 10.1002/cam4.1814
|View full text |Cite
|
Sign up to set email alerts
|

The role of tissue and serum carcinoembryonic antigen in stages I to III of colorectal cancer—A retrospective cohort study

Abstract: PurposeTissue carcinoembryonic antigen (t‐CEA) and serum carcinoembryonic antigen (s‐CEA) expression profiles are the most useful tumor markers for the diagnosis and evaluation of colorectal cancer (CRC) worldwide; however, their roles in CRC progression remain controversial. This study aimed to compare the prognostic values of both s‐CEA and t‐CEA in CRC.MethodsA total of 517 patients from January 2006 to December 2010 with stages I‐III CRC were retrospectively examined, with 5‐year postoperative follow‐up an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 49 publications
(74 reference statements)
1
43
1
Order By: Relevance
“…Five-year DFS and OS were analyzed by the Kaplan-Meier method and the Breslow test. Survival rates were equally assessed by multivariable Cox's regression according to various clinical, pathological, and biochemical parameters, which were analyzed in our previous studies (21,26). Patient statuses were divided into two: i) Only death was considered an event, and other parameters were censored for OS analysis; ii) death and recurrence were considered events, and other parameters were censored for DFS analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five-year DFS and OS were analyzed by the Kaplan-Meier method and the Breslow test. Survival rates were equally assessed by multivariable Cox's regression according to various clinical, pathological, and biochemical parameters, which were analyzed in our previous studies (21,26). Patient statuses were divided into two: i) Only death was considered an event, and other parameters were censored for OS analysis; ii) death and recurrence were considered events, and other parameters were censored for DFS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…prognosis in CRC (25,26), Ki67 is broadly employed in pathological analyses to evaluate cell proliferation in various malignancies (27)(28)(29)(30). Although Ki67 is expressed in benign tumors, its levels are very low; however, it is found at high levels in multiple malignant lesions, and tightly associated with distant metastasis, resulting in poor patient prognosis.…”
Section: Cutoff Of 25% For Ki67 Expression Is a Good Classification Tmentioning
confidence: 99%
“…Recent studies have noted that CEA is insufficiently sensitive to be used alone, and some researchers have sought new ways to improve its prognostic value by the addition of another factor, such as CD44v6, carbohydrate antigen (CA) 19-9, neutrophil-to-lymphocyte ratio (NLR), or peritoneal carcinomatosis index ratio (PCI)[6,8-11]. Intriguingly, a recent study indicated that postoperative tissue CEA (t-CEA) rather than serum CEA (s-CEA) is an independent prognostic factor in stage I to III CRC[12]. This indicated that we should pay more attention to the local CEA produced by tumor cells rather than the overall serum CEA level.…”
Section: Introductionmentioning
confidence: 99%
“…91 Novel Targeted Therapy and Drug Delivery Vehicles mABs against CEA, a membrane-anchored glycoprotein, such as labetuzumab, aim to target payloads to tissue CEA which is overexpressed in over 90% of CRC. 92 Such payloads include targeted photodynamic therapy, radio-guided surgery, and radioimmunotherapy for peritoneal metastases. [93][94][95] A phase 1/2 trial using the payload govitecan (a liposomal irinotecan metabolite) demonstrated tumor response in 38% of the 72 patients enrolled, with SD in 48%.…”
Section: Using Novel Agentsmentioning
confidence: 99%